Полісемія та омонімія в українській астрономічній термінології - Богуш, Оксана; Bohuch, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті зосереджено увагу на явищах полісемії та омонімії в українській астрономічній термінології кінця ХІХ – першої третини ХХ століття. На основі аналізу семантичної структури наявних у терміносистемі астрономії полісемічних слів виділено зовнішньосистемну, міжсистемну та внутрішньосистемну полісемію, а також описано міжгалузеву та внутрішньосистемну омонімію.The article focuses on the phenomenon of polysemy and homonymy in terminology Ukrainian аstronomical late XIX – the first third of the twentieth century. Analyzes semantic distinction between these phenomena. It is proved that each value polisemichnoho words necessarily linked to its initial value. The main route is the formation of homonyms multiple-splitting semantic structure units. Described zovnishnosystemnu, intersystem and intra polysemy and intra and inter-homonyms. Interconnect multiple meaning and homonymy is dangerous for astronomical terminology, they create unambiguous content povidomlyuvanoho. Studying the phenomena of polysemy and homonymy is relevant for the systematization, standardization and unification of Ukrainian astronomical terminology, and the need for further development of Ukrainian terminology.
Polysemy and homonymy in the Ukrainian astronomical terminology
Keywords: українська астрономічна термінологія; термін; полісемія; омонімія; семантична структура; Ukrainian astronomical terminology; term; polysemy; homonymy; semantic structure